2006
DOI: 10.1096/fj.06-5895fje
|View full text |Cite
|
Sign up to set email alerts
|

Differential role of Jak‐STAT signaling in retinal degenerations

Abstract: Retinal degeneration is a major cause of severe visual impairment or blindness. Understanding the underlying molecular mechanisms is a prerequisite to develop therapeutic approaches for human patients. We show in three mouse models that induced and inherited retinal degeneration induces LIF and CLC as members of the interleukin (IL)-6 family of proteins, activates proteins of the Jak-STAT signaling pathway, and up-regulates suppressors of cytokine signaling as a negative feedback loop. Inhibition of Jak2 leads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
112
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(126 citation statements)
references
References 61 publications
12
112
0
2
Order By: Relevance
“…JAKMIP1 interacts with Tyk2, a member of Janus kinase family, which has been shown to control the survival and proliferation of retinal cells (Samardzija et al, 2006). LIFR, together with its ligand, leukemia inhibitory factor (LIF), also participates in neuroprotection by activating an endogenous rescue pathway that protects viable photoreceptor cells (Bürgi, Samardzija, & Grimm, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…JAKMIP1 interacts with Tyk2, a member of Janus kinase family, which has been shown to control the survival and proliferation of retinal cells (Samardzija et al, 2006). LIFR, together with its ligand, leukemia inhibitory factor (LIF), also participates in neuroprotection by activating an endogenous rescue pathway that protects viable photoreceptor cells (Bürgi, Samardzija, & Grimm, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Exposure to high levels of white light induces photoreceptor degeneration and activates a signaling cascade which includes leukemia inhibitory factor (LIF), Janus kinase 2 (Jak2), signal transducer and activator of transcription 1 (STAT1) and STAT3 (Samardzija et al, 2006a). A similar retinal response has been observed in models of inherited retinal degeneration (Samardzija et al, 2006a).…”
Section: Introductionmentioning
confidence: 86%
“…Growth factor-induced activation of Akt has been shown in transformed retinal neurons (Barber et al, 2001) and mouse models of retinal degeneration (Samardzija et al, 2006). In situ hybridizations have shown that all three Akt mRNAs are present in different layers of the retina (Reiter et al, 2003).…”
Section: Introductionmentioning
confidence: 99%